Mindfulness in Surgery. Issue 6 (November 2019) - Stephen, Antonia E.; Mehta, Darshan H.
In the past 20 years, interest in mindfulness and its cultivation through various meditative practices has increased astronomically. This is reflected in the popularity of mindfulness training programs, its ever-widening exposure in popular culture, and in the number of scientific articles published on the topic. With the recent focus on burnout in the medical profession and reports of high levels of anxiety and depression among residents and staff physicians, the potential applications of mindfulness are becoming increasingly apparent in the hospital setting. Mindfulness meditation may be particularly useful for surgeons because they are required to maintain their presence of mind and mental focus in the setting of challenging physical and mental tasks. Furthermore, personality traits such as perfectionism and intensity, which may have facilitated success in the competitive environment of medical school and residency training, may later manifest as intolerance and impatience, contributing to frustration and anger. A mindfulness meditation practice may help reduce the tendency to react to these emotions, yet still allow surgeons to remain motivated to excel. This article provides a definition of mindfulness and describes its introduction to Western culture. The connection of a regular meditation practice to improvements in focus and performance are reviewed. The potential benefits of mindfulness training to a surgical career are discussed, and an approach to introducing mindfulness and meditation to individual surgeons and surgical departments is outlined. We hypothesize that the introduction of department-wide training programs in mindfulness and meditation could benefit surgeons with regard to technical performance, empathy toward patients, academic productivity, and general life and career satisfaction.